2017
DOI: 10.1111/wej.12288
|View full text |Cite
|
Sign up to set email alerts
|

Repeated phosphate removal from recirculating aquaculture system using cyanobacterium remediation and chitosan flocculation

Abstract: Unicellular cyanobacterium Synechocystis sp. was used for phosphate removal in a recirculating aquaculture system. The cell harvesting was performed using chitosan solution in this study. The parameters (i.e. cell density, pH of cell suspension and chitosan concentration) affecting the flocculation efficiency of chitosan were investigated. With the optimal condition, the repeated flocculation for phosphate removal in a photobioreactor was demonstrated. The results show that the flocculation efficiency of chito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
1
4
1
Order By: Relevance
“…Overall, treatment with chitosan was sufficient to sediment 97 ± 2% of the culture biomass across both experiments with initial culture densities (OD 750 ) ranging between 1.9 and 4.1. The observed flocculation efficiencies were slightly better than those previously reported for Synechocystis (>90%) using 15 or 20 mg L -1 of chitosan at pH 7.0–7.2 ( Divakaran and Pillai, 2002 , Rojsitthisak et al, 2017 ). To the best of our knowledge, this is the first study to show that temporary culture pH adjustment using CO 2 is sufficient to significantly increase flocculation efficiency.…”
Section: Resultscontrasting
confidence: 69%
See 1 more Smart Citation
“…Overall, treatment with chitosan was sufficient to sediment 97 ± 2% of the culture biomass across both experiments with initial culture densities (OD 750 ) ranging between 1.9 and 4.1. The observed flocculation efficiencies were slightly better than those previously reported for Synechocystis (>90%) using 15 or 20 mg L -1 of chitosan at pH 7.0–7.2 ( Divakaran and Pillai, 2002 , Rojsitthisak et al, 2017 ). To the best of our knowledge, this is the first study to show that temporary culture pH adjustment using CO 2 is sufficient to significantly increase flocculation efficiency.…”
Section: Resultscontrasting
confidence: 69%
“…from 2.09 to 0.52), indicating that pH and/or the growth medium composition was suboptimal for efficient flocculation. As chitosan is most effective in a pH range from 6.0 to 7.2 ( Divakaran and Pillai, 2002 , Rojsitthisak et al, 2017 ), 10% CO 2 was bubbled though the culture medium to temporarily reduce the pH to 6.8. Subsequent addition of chitosan resulted in a 95 ± 1% reduction in culture density.…”
Section: Resultsmentioning
confidence: 99%
“…Synechocystis sp. was shown to remove phosphate in a recirculating aquaculture system [47], and other cyanobacterial species were shown to reduce the nitrogen content of dairy wastewater by circa 80% [48]. In accordance with these results, these results suggest that cyanobacteria might offer a potential solution for nitrogen and phosphorus removal from wastewaters.…”
Section: Discussionsupporting
confidence: 71%
“…In other studies, 250 mg of chitosan per g of stationary culture Synechocystis was required to achieve over 90% flocculation efficiency [ 34 ]. Another study on the same strain revealed that for flocculation efficiency exceeding 90% to be achieved within 1 h of settling requires a final chitosan concentration of at least 5 mg L −1 [ 35 ]. Interestingly, 90% flocculation efficiency in 1 h has also been achieved for the marine strain Synechococcus elongatus BDU 130192 when treated with a 16 mg L −1 final concentration of chitosan.…”
Section: Discussionmentioning
confidence: 99%